In negative life contexts men report a lower desire to end relationship if their partners are high in borderline behavioral characteristics. A quasiexperimental research - Burtaverde, Vlad; Shackelford, Todd K.; Ionescu, Ștefan-Cosmin; Bumbănac , Maria; Avram, Eugen (Studia Psychologica: Theoria et praxis, 2022)
We investigated the relationship between borderline symptoms in women and their partner’s desire to continue the relationship and relationship commitment in an aversive living environment using an experimental design. We aimed to highlight the adaptive mechanisms of borderline symptoms, which may materialize in reproductive advantages for women in aversive contexts. We conducted two experiments to test the same hypotheses. In Study 1, online participants were assigned to the experimental group (N = 123). The experimental scenario hypothesized having a relationship with a woman high in borderline characteristics, during an aversive life environment. The control group (N = 118) hypothesized having a relationship with a woman high in borderline characteristics, during normal living conditions. We repeated the same experimental manipulation using a within-subjects design in Study 2 (N = 171). Environmental conditions influenced the desire to end the relationship with women characterized by borderline symptoms; men had a lower desire to end the relationship with their partner in aversive life events than in normal living conditions. Thus, women’s borderline behavioral characteristics may bring mating benefits in aversive living environments.